EFEKTIVITAS PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENYALAHGUNAAN BAHAN BAKAR MINYAK BERSUBSIDI (Studi Pada Satuan Reserse Kriminal Kepolisian Resor PasamanBarat) - Randhya Sakthika Putra; Iyah Faniyah; Adhi Wibowo (Program Magister Ilmu Hukum Universitas Ekasakti, 2019)
Act Number 22 Year 2001 on Oil and Natural Gas regulated on prohibited and threatening acts with criminal sanctions for anyone who violates them. One of the prohibited acts is to commit criminal misuse of subsidized fuel oil (BBM). To be able to qualify such action, the police as investigator must pay attention to the elements of the provisions of Article 23 and Article 53 letter b and Article 55, so that will realize the effectiveness of law enforcement on the crime of misuse of subsidized fuel through the process of investigation with all the constraints faced in law enforcement.